Contemporary Batik on The Verge of Risk: The Urgency of Copy Right Registration for Legal Protection - Indrawati, Septi; Nisrina, Wanda Athaya; Rachmawati, Amalia Fadhila (JUSTITIA JURNAL HUKUM, 2024)
Contemporary batik is characterised by motifs or patterns containing freedom of expression, not bound by tradition and patterns that tend to be more modern. In Purworejo Regency, there are 48 contemporary batik craftsmen, but only 6 craftsmen have copyright certificates for their contemporary batik motifs. While other craftsmen do not yet have a copyright certificate. Though copyright is a legal protection needed for a work, one of them contemporary batik. Copyright is an exclusive right granted to the copyright holder to use, reproduce or give permission for it on a work. This study aims to analyse the legal protection of contemporary batik through copyright registration. To achieve these goals, this research was conducted using normative sociological legal research methods. Normative sociological means that the research is conducted by examining existing legal materials, then analysing how its implementation in society in accordance with the problems faced. Legal materials collected will be reviewed comprehensively and analysed deductively with a systematic presentation. The results showed that copyright registration provides legal protection against contemporary batik motifs. Through this copyright registration, the creator will get a copyright certificate, where the certificate can be proof of legal ownership of batik motifs. Legal protection provided in the form of preventive protection, namely prevention so that no one else who imitates the contemporary batik motif. Furthermore, protection repressive, namely case settlement can be done through the path of litigation or non-litigation when there is a case related to batik motifs contemporary.